PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS I SDN 2 TEGAL GONDO - Anggi, Novita; Binti Khoiriyah; Nurkaif (STKIP Subang, 2026)
Reading ability is a fundamental skill that must be mastered by elementary school students, especially in the early grades. However, based on observations conducted in Grade I of UPTD SDN 2 Tegal Gondo, many students still experience difficulties in reading letters, vocabulary, and simple sentences. One of the causes is the use of less engaging teaching methods and the lack of supporting learning media. This study aims to improve the reading ability of Grade I students through the use of picture media in Indonesian language learning. This study employs Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 14 Grade I students of UPTD SDN 2 Tegal Gondo. Data collection techniques included observation, interviews, tests (pre-test and post-test), and documentation. The indicators of reading ability measured included reading vowel letters, reading vocabulary, reading simple sentences, and reading with correct pronunciation and intonation. The test analysis results showed that in Cycle I, the average reading ability of students reached 52.75% and had not yet met the success indicator set at 80%. After improvements were made in Cycle II, the analysis results showed an average increase to 88.25%. This 35.5% improvement indicates that the use of picture media is effective in enhancing students’ reading ability.